Analysis of the Sequence Specificities of DNA Binding Proteins with Protein Binding Microarrays - Bulyk, Martha L. (2006)
DNA binding proteins are important for various cellular processes, such as transcriptional regulation, recombination, replication, repair, and DNA modification. Of particular interest are transcription factors (TFs), since through interactions with their DNA binding sites, they modulate gene expression in a manner required for normal cellular growth and differentiation, and also for response to environmental stimuli. To date, the DNA binding specificities of most DNA binding proteins remain unknown, since earlier technologies aimed at characterizing DNA-protein interactions have been laborious and not highly scalable. Recently we developed a new DNA microarray-based technology, termed protein binding microarrays (PBMs), that allows rapid, high-throughput characterization of the in vitro DNA binding site sequence specificities of TFs, or any DNA binding protein. The DNA binding site data from PBMs can be used to predict what genes are regulated by a given TF, what the functions are of a given TF and its predicted target genes, and how that TF may fit into the cell's transcriptional regulatory network.